2022
DOI: 10.1055/s-0042-1757197
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Is Effective for Postcolectomy Recurrent Clostridioides difficile Infection

Janice Cho,
Maria Vazquez Roque,
Robert Orenstein
et al.

Abstract: Background The outcomes from fecal microbiota transplantation (FMT) for recurrent Clostridioides difficile infection (rCDI) in patients after complete or partial colectomy are not well-defined. Objectives We sought to report our experience with FMT for rCDI in patients who have undergone colectomy. Methods Descriptive analyses of FMT outcomes from 2014 to 2020 were performed in patients who previously had undergone complete or partial colectomy. Results Twenty-nine patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…They reported that two patients (6.9%) had rCDI within 8 weeks post-FMT, seven had CDI beyond 8 weeks (median 10 months) with 71% related to antibiotic exposure post-FMT, and resolution in others, thereby suggesting a 69% overall success. 11 Therefore, this study although a retrospective analysis does add to the sparse data on the role of FMT in this subset of patients.…”
mentioning
confidence: 99%
“…They reported that two patients (6.9%) had rCDI within 8 weeks post-FMT, seven had CDI beyond 8 weeks (median 10 months) with 71% related to antibiotic exposure post-FMT, and resolution in others, thereby suggesting a 69% overall success. 11 Therefore, this study although a retrospective analysis does add to the sparse data on the role of FMT in this subset of patients.…”
mentioning
confidence: 99%